(untitled) (Web of Scientists and Scholars: Journal of Multidisciplinary Research, 2025)
This article explores the legal concept of priority rights in trademark law by comparatively analyzing the “first-to-use” and “first-to-file” principles. The study examines how the United States, the United Kingdom, Japan, Germany, and Russia regulate trademark registration and establish priority, drawing on statutory frameworks such as the Lanham Act, the Trade Marks Act 1994, and the Trademark Act of 1959. It also evaluates the role of international treaties, particularly the Madrid Agreement and the Madrid Protocol, in harmonizing cross-border trademark protection. Scholarly perspectives from McCarthy, Tushnet, Lemley, Schricker, Beier, and others are reviewed to highlight the advantages and drawbacks of each model. The analysis concludes by identifying core legal challenges—such as evidentiary burdens, territorial limitations, and registration-based trolling—and offers policy recommendations aimed at balancing formal registration with genuine commercial use in both national and international contexts.